Capital Market Responses to the G20 Summit Events in Indonesia: An Analytical Study - Cahyani, Ni Ketut Bintang; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 35 No 5 (2025)DO - 10.24843/EJA.2025.v35.i05.p02, 2025)
By calculating abnormal return, the study aims to analyzing how the capital market responded to the large holding of the G20 Indonesia Summit both before and after the event. With an observation duration of eleven days, this study is an event study. Sampling was carried out purposively to select 76 energy sector issuers listed on the Indonesia Stock Exchange. The Wilcoxon signed ranks test was used to evaluate the data. Based on study findings, the average abnormal return before and after Indonesia hosted the G20 Summit did not differ. The findings of this study indicate that information from the G20 Summit has not been considered important enough to influence the market. Investors are able to anticipate the energy transition agreement during the G20 Summit so that they do not rush to invest around the event. Keywords: Event Study, Market Reaction, Abnormal Return, G20 Summit.